Creation Features of Devices for Testing Nasal Breathing - Аврунін, О. Г.; Носова, Я. В.; Тимкович, М. Ю.; Худаєва, С. А.; Glasmacher, B.; Ibrahim Younouss Abdelhamid (ХНУРЕ, 2020)
The paper is devoted to the questions of metrological certification of tests of the device of rhinomanometry type PRX. The main stages of the methodology of metrological certification, as well as design and technological aspects in the development of rhinomanometers with a measuring unit are described.
Keywords: respiratory; nasal breathing; pressure drop; rhinomanometry